Does ESG performance have an impact on financial performance? Evidence from Turkey - Melih Sefa Yavuz; Hasan Sadık Tatlı; Gözde Bozkurt; Gökten Öngel (Journal of Entrepreneurship, Management and Innovation, 2025)
PURPOSE: Stakeholders such as consumers, nongovernmental organizations, and public institutions have increasingly pressured companies to adopt corporate social responsibility (CSR) policies. This trend has led to the integration of environmental, social, and governance (ESG) reporting into business strategies to achieve long-term competitive advantages and enhance financial performance. ESG reporting has become a critical tool for measuring corporate CSR efforts, contributing to the institutionalization of nonfinancial reporting standards. This study aims to determine how the adoption of ESG sub-dimensions affects the financial performance of companies in Turkey. METHODOLOGY: The study employed panel regression analysis on data from 21 companies listed in the Borsa Istanbul-100 index over the period 2011–2020 to investigate the relationship between ESG sub-dimensions and firm performance. FINDINGS: The findings indicate that adopting the environmental and governance sub-dimensions positively affects ROE and Tobin’s Q. However, the adoption of the governance sub-dimension negatively impacts Tobin’s Q while positively influencing ROE. No statistically significant results were found regarding the impact of ESG sub-dimensions on firms’ ROA ratios. IMPLICATIONS: The results of the research, based on the example of Turkey, are important to determine how companies’ social responsibility strategies in developing countries provide them with outputs in terms of environment, social and governance and whether social responsibility-based activities are truly sustainable strategy for companies in developing countries.The findings highlight the importance of considering the macroeconomic structure, legal system, and financial development of countries when evaluating CSR activities. The regulatory environment plays a significant role, as weaker legal protections can negatively affect the relationship between governance practices and firm performance. For practitioners, the insights suggest prioritizing environmental investments and carefully strategizing governance practices to align with investor expectations and regulatory frameworks. ORIGINALITY AND VALUE: By focusing on the BIST 100 companies, this study contributes to the limited literature on the role of ESG sub-dimensions in shaping financial performance in developing markets. This research provides valuable insights into how environmental, social, and governance practices specifically impact the financial outcomes of firms in Turkey, offering a nuanced understanding that can inform both academic discussions and practical strategies in similar contexts.